1981
DOI: 10.3758/bf03212025
|View full text |Cite
|
Sign up to set email alerts
|

Activity differences of individually and group-housed male and female rats

Abstract: Previous comparisons of the activity differences of individually and group-housed rats have produced inconsistent findings; therefore, we examined activity using three measures: openfield ambulation, nonspecific circadian activity, and rearing behavior. Open-field ambulation in two 5·day tests confirmed our prediction that isolates would be initially less active but later more active than group·housed rats. Isolates habituated more slowly to the activity monitor and tended to be more active during the light ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
(27 reference statements)
1
16
1
Order By: Relevance
“…The behavioural assessments in this study, necessarily performed at 14 days of treatment since single-housing could alter responses (Einon et al, 1975;Dalrymple-Alford & Benton, 1981;Gentsch et al, 1982), provided independent confirmation of the efficacy of drug treatments. Sedative and anti-anxiety effects are commonly associated with the administration of tricyclics to patients or animals; such actions need not correlate with antidepressant activity .…”
Section: Discussionmentioning
confidence: 86%
“…The behavioural assessments in this study, necessarily performed at 14 days of treatment since single-housing could alter responses (Einon et al, 1975;Dalrymple-Alford & Benton, 1981;Gentsch et al, 1982), provided independent confirmation of the efficacy of drug treatments. Sedative and anti-anxiety effects are commonly associated with the administration of tricyclics to patients or animals; such actions need not correlate with antidepressant activity .…”
Section: Discussionmentioning
confidence: 86%
“…Although an increase in ambulation during the social interaction test was observed between isolated and group-housed rats, when they were tested with a conspecific of a similar housing background, no difference in ambulation was present when an isolated rat was tested with a group-housed partner. Thus the increase in social activity is a specific increase in gregariousness and not due to a general hyperactivity of the isolated animals, as is reported to occur after prolonged isolation although this response has been questioned [5,6,13,14,30]. The duration of the isolation period therefore may be important for changes in locomotor activities (see also [28]).…”
Section: Fig 3 Correlation Diagram Comparing Frequency and Durationmentioning
confidence: 98%
“…However, the direction and significance of some of these behavioral and physiological parameters have been a matter of debate. Thus, DalrympleAlford and Benton [5,6] showed an initial reduced locomotor activity of isolated rats, while other investigators reported an increased activity only [14]. In most of these studies long-term individually housed animals were used and the differences with group-housed animals were apparent only after weeks or sometimes even months of individual housing.…”
Section: Social Interactionmentioning
confidence: 99%
“…Since then, it has been shown to affect a wide range of physiological variables such as blood pressure and heart rate (Woodworth and Johnson, 1988), circadian rhythms (Greco et al, 1989), sexual maturation (Swanson and van de Poll, 1983), body weight and life span (Menich and Baron, 1984;Moon et al, 2006), drug responsiveness (Juraska et al, 1983), and immune system activity (Jessop and Bayer, 1989). It also affects behavioral measures such as spontaneous pup retrieval (Herrenkohl and Lisk, 1973), sexual activity (Spevak et al, 1973;Swanson and van de Poll, 1983), morphine self-administration (Alexander et al, 1978), and open-field activity (Dalrymple-Alford and Benton, 1981;Menich and Baron, 1984;Thorsell et al, 2006). Social isolation has consequences for the brain as well, including decreased expression of neuropeptide Y (Thorsell et al, 2006) and neuroactive steroids (Serra et al, 2007), and decreased spine density in cortical pyramidal neurons (Silva-Gomez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%